Contribuições do Movimento dos Focolares ao ecumenismo - Simões, Beatriz Sarkis (2010)
This research aims to give greater visibility to the specific contributions that the Focolare Movement, founded in 1943 by Chiara Lubich, has to offer to the ecumenical journey. The first part deals with the history of ecumenism: the concept, historical events that also led to ruptures in the Church of Christ, the genesis of the ecumenical movement and the relevance of ecumenism. Analyzing the importance of ecumenical dialogue, this research presents the proposal of the dialogue of life which has its roots in the spirituality of the Focolare Movement and is considered one of its specific contributions to ecumenism. The second part presents an ecumenical hermeneutics which has two principles: fraternity and cross. It is believed that it is not possible to reach full communion (koinonia), without going through the way of the cross, through the way of the abandonment of Jesus (kenosis). Then a reflection on the Focolare Movement and the ecclesiology of communion is made. The reflection leads to the central topic of this chapter: the proposal of the dialogue of life presented as an answer to the demands of the current ecumenical world. The third part presents a second specific contribution of the Focolare Movement to the ecumenical journey: the Project of the Economy of Communion in Freedom, which was launched in 1991 by Chiara Lubich during one of her trips to Brazil. This social Project, which is put into practiced ecumenically, is present in several countries around the world today and reflects the reality of communion which is the basis proposed by the spirituality of the Focolare Movement. So, it is possible to asseverate that the Focolare Movement has something significant to offer to the ecumenical journey, whether on a spiritual or a practical level.